The Sereni Smart Bracelet: A Multimodal Sensory Wearable for Autoregulation inIndividuals with Autism Spectrum Disorder: The Sereni Smart Bracelet: A Multimodal Sensory Wearable for Autoregulation inIndividuals with Autism Spectrum Disorder - Kiehl, Isabella Tocchini (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
Background: Individuals with Autism Spectrum Disorder (ASD) frequently experience challenges with sensory processing, emotional regulation, communication, and focus, often leading to significant distress or "meltdowns." Existing market solutions for sensory support are typically single-functional, often stigmatizing, and lack the discreet, portable design necessary for continuous use across diverse environments. Objective: This paper introduces the Sereni smart bracelet, a novel, multi-functional, and discreet wearable device conceptualized to provide personalized sensory stimuli (vibration, ASMR/binaural sounds, and light) to support autoregulation, improve focus, and aid in crisis prevention for neurodivergent individuals, particularly those with ASD across all support levels. Methods: We employed a user-centered design (UCD) approach informed by identified needs of autistic individuals and their families, as well as established principles of sensory intervention. The Sereni bracelet integrates three core sensory modalities: a central button for customizable vibrations (targeting therapeutic frequencies between 40-120 Hz), a lateral output for user-selected ASMR and binaural sounds, and integrated lights around the main button for visual distraction. The design prioritizes discreetness, personalization through interchangeable bands, and user comfort (hypoallergenic silicone). Results: The Sereni bracelet is positioned as an innovative "blue ocean" solution, addressing a significant market gap for a comprehensive, multi-functional, and non-stigmatizing sensory aid. Its design directly tackles the critical need for a tool that offers continuous support without drawing unwanted attention. The multimodal stimuli are grounded in established evidence for sensory interventions in ASD, including specific vibration frequencies for calming, the benefits of music therapy and light therapy. The integration of userselectable functions caters to individual sensory profiles, promoting self-management and independence. Conclusions: The Sereni smart bracelet offers a promising, user-centered approach to sensory support for individuals with ASD. By empowering self-regulation through discreet, customizable sensory input, it has the potential to reduce crisis severity, improve focus, and enhance overall quality of life for both autistic individuals and their families. This project aims to bridge the gap between therapeutic needs and practical, socially acceptable wearable technology.